Ureteral stump syndrome after ureteroureteroanastomosis, heminephrectomy and nephrectomy in children - I. V. Kagantsov; D. N. Shchedrov; V. V. Sizonov; V. I. Dubrov; S. G. Bondarenko; G I. Kuzovleva; A. V. Pirogov; V. G. Svarich; V. M. Orlov; O. V. Staroverov (Вестник урологии, 2020)
Introduction. Nephrectomy (NE), heminephrectomy (HNE) and the formation of ipsilateral ureteroureteroanastomosis (UUA) do not exclude the possibility of preserving the distal ureter. The remaining ureteral stump can cause the formation of ureteral stump syndrome (USS) in the form of recurrent urinary tract infection (UTI), hematuria, pain syndrome, and stump empyema in some cases.Purpose of the study. To assess the incidence and treatment approach of USS in children after NE, HNE and UUA performed using open and laparoscopic access in different Russian clinics.Material and methods. The study is based on the results of treatment of 778 patients from 9 clinics in the Russian Federation and the Republic of Belarus in the period from 1998 to 2020. Patients underwent NE, HNE and UUA by open or laparoscopic access. The ureter was not removed completely, its stump was left. Open access was used in 313 (40.2%) children, laparoscopic in 465 (59.8%) cases. USS was detected in 27 (3.5%) patients. The ureteral stump was removed in 26 (96.3%) children. Open removal of the ureteral stump was performed in 11 (42.3%) patients, through laparoscopic access in 13 (50.0%) and vesicoscopically in 2 (7.7%) children.Results. There were 12 boys (44.4%) and 15 girls (55.6%) among the patients with USS. USS was detected on the right in 13 (48.1%) children, on the left - in 14 (51.9%). The median age of the patients was 25 [12; 42] months at the time of USS detection. Ureteral stump was sutured and ligated in 15 (55.6%) children during the primary operation, the stump was left open after excision in 4 (14.8%) children, it was not indicated how the stump was processed in 8 (29.6%) patients. Reflux to the stump was detected in 13 (48.1%) patients, USS against the background of obstruction was detected in 14 (51.9%) children. It was determined that the frequency of SCM is lower (9 (1.9%)) with the use of laparoscopic access than with open (18 (5.8%)) operations (p < 0.004). Clinical manifestations occurred in 85% of patients with USS within a year after surgery.Conclusion. USS is a rare complication (3.5% of cases) in patients who have undergone NE, HNE and UUA with the distal ureteric stump preserving. Performing these operations by laparoscopic access allows carrying out total ureterectomy and significantly reduces the likelihood of USS development.